EFFECT OF SOME MEDICINAL PLANTS ON LABORATORY ANIMALS EXPOSED TO ALUMINUM POISONING - Abd-Alhadi Ibrahim Hussein Al Jumaily1, Adnan Mohammed Ahmeed Aldulaimi1 (Chelonian Research Foundation, 2024)
Aluminum is recognized as a public health concern because of its potential toxic effects on human health. Therefore, the current experiment was conducted to investigate the effectiveness of medicinal plants that include Cucurbita pepo and Ganoderma lucidum in reducing the toxicity induced by aluminum chloride (AlCl3) in animals. In this experimental study, thirty male rats were allocated to six groups. no treatment (control), AlCl3 (40 mg/kg B.W.), Cucurbita pepo, Ganoderma lucidum, Cucurbita pepo +AlCl3, Ganoderma lucidum+AlCl3, for 28 days. On the final day, animals were sacrificed, Indices of body weight, liver, kidney, spleen, blood component parameters, biochemical parameters of liver and kidney function, and antioxidants were estimated. AlCl3 treatment resulted in a significant decrease (P>0.05) in the values of RBCs, HCB, HCT, MCV, MCH, MCHC, GRAN PLT and Glutathione. a significant increase in WBC, MON and liver, kidney, body weight, uric acid, Urea, Creatinine, ALT, AST, ALP and Malondialdehyde. There was no significant difference in LYM and Spleen weight compared with the control group. As for the groups of both Cucurbita pepo+ Aluminum chloride and Ganoderma lucidum+ Aluminum chloride led to a significant decrease in WBC, MON, uric acid, Urea, Creatinine, ALT, AST, ALP and Malondialdehyde. Increase in body weight, RBCs, HCB, HCT, MCV, MCH, MCHC, GRAN, PLT and Glutathione. No significant difference in Spleen weight and LYM comparison with the group infected with aluminum chloride poisoning. The present study concluded that Cucurbita pepo and Ganoderma lucidum had beneficial effects as they were able to reduce cadmium chloride toxicity in male rats. Key word: Cucurbita pepo, Ganoderma lucidum, aluminum chloride, haematological, Biochemical parameters.